2021
DOI: 10.3389/fmicb.2021.632280
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Dynamics of Soybean (Glycine max) Is Affected by Cropping Sequence

Abstract: The microbial composition of the rhizosphere soil could be an important determinant of crop yield, pathogen resistance, and other beneficial attributes in plants. However, little is known about the impact of cropping sequences on microbial community dynamics, especially in economically important species like soybean. Using 2-year crop sequences of corn-soybean, canola-soybean, and soybean-soybean, we investigated how crops from the previous growing season influenced the structure of the microbiome in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…In the present study also a similar microbial abundance was found. Analogously, Bolaji et al (2021) reported Actinobacteria, Proteobacteria, and Acidobacteria as the dominant taxa in canola, corn, and soybean crop rotation planting systems.…”
Section: Cropping Sequences Changed the Diversity And Composition Of ...mentioning
confidence: 78%
See 3 more Smart Citations
“…In the present study also a similar microbial abundance was found. Analogously, Bolaji et al (2021) reported Actinobacteria, Proteobacteria, and Acidobacteria as the dominant taxa in canola, corn, and soybean crop rotation planting systems.…”
Section: Cropping Sequences Changed the Diversity And Composition Of ...mentioning
confidence: 78%
“…Xie et al (2022) found that the crop rotation stage strongly affected the soil microbial community structure and assembly compared to that of the fertilization regime. The cropping sequences within the rotation can change soil microbial communities and give favorable impacts for increased agronomic performance (Bolaji et al, 2021). Microorganisms have been shown to improve plant development by secreting metabolites, mobilizing nutrients, and alleviating biotic and abiotic stresses (Tahir et al, 2017;Bolaji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-four sequences of the soil microbiome of rice have been characterized by metagenomics [ 73 ]. Nevertheless, the metagenome-based approach provides new insights into the variation of fungal populations, bacterial diversity, and their richness in both the bulk soil and rhizosphere of soybean [ 74 ], the effects of continuous sugar beet cultivation on its endophytes [ 75 ] and the assessment of rhizosphere diversity and endophytic fungi in Atractylodes macrocephala [ 76 ].…”
Section: Metagenomics and Metatranscriptomics: A Paradigm Shift In Mi...mentioning
confidence: 99%